Letter from Marianne and Viktor Homburger to Max Bredig, May 30, 1940 - Homburger, Marianne; Homburger, Viktor (1940)
The Homburger family wishes Max Bredig (1902-1977) and Georg Bredig (1868-1944) well in their new home in New York City. Marianne Homburger additionally discusses emigration difficulties in Germany.
Keywords: Homburger, Viktor, 1888-1968; Homburger, Marianne, 1903-1986; Bredig, Max Albert, 1902-1977; Emigration and immigration